2014
DOI: 10.4103/0019-509x.146723
|View full text |Cite
|
Sign up to set email alerts
|

Toward better quality of anticancer generics in India

Abstract: Treatment of cancer is limited by affordability of patients in the many developing countries including India. Generic drug manufacturers have responded to this scenario by making drugs available at affordable costs, often at less than 10% the cost of the original brand. In our practice, it is found that there is a three-fold higher prescription of generic brands compared to innovator, accompanied by cost savings of up to 80% per prescription. Unfortunately, the regulatory environment prevailing in India is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Additionally, there is no strict definition of comparability as there is for oral formulations. It is left up to the SLA in many cases to determine the quality control measures necessary to approve a drug in their state which has led to heterogeneous practices throughout India and possibly a lax regulatory environment …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is no strict definition of comparability as there is for oral formulations. It is left up to the SLA in many cases to determine the quality control measures necessary to approve a drug in their state which has led to heterogeneous practices throughout India and possibly a lax regulatory environment …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall affordability for both OBs and LPGs was found to be 55.5% which makes cancer a catastrophic disease for local masses [ 33 ]. Another dilemma of LMICs is that the local masses are unaware of the importance of health insurance [ 34 ]. But sometimes these insurance policies fail to provide benefits or demand substantial co-payment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another dilemma of LMICs is that the local masses are unaware of the importance of health insurance. 39 Insurance policies fail to provide benefits or demand substantial copayment. 40 Therefore, in 2014 the Pakistani government took an initiative in the form of the Prime Minister National Health Insurance Program.…”
Section: Discussionmentioning
confidence: 99%